2006
DOI: 10.4049/jimmunol.177.8.5652
|View full text |Cite
|
Sign up to set email alerts
|

Triosephosphate Isomerase- and Glyceraldehyde-3-Phosphate Dehydrogenase-Reactive Autoantibodies in the Cerebrospinal Fluid of Patients with Multiple Sclerosis

Abstract: Our previous results revealed that Igs in lesions and single chain variable fragment Abs (scFv-Abs) generated from clonal B cells in the cerebrospinal fluid (CSF) from patients with multiple sclerosis (MS) bind to axons in MS brains. To study the axonal Ags involved in MS, we identified the glycolytic enzymes, triosephosphate isomerase (TPI) and GAPDH, using Igs from the CSF and scFv-Abs generated from clonal B cells in the CSF and in lesions from MS patients. Elevated levels of CSF-Abs to TPI were observed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 52 publications
0
40
0
Order By: Relevance
“…Until now, information on involvement of specific Ags in MS has been limited. More recently, other CNS Ags have been identified that are potential biomarkers in MS (19,20). The role of these Ags in MS pathogenesis is currently being further studied.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…Until now, information on involvement of specific Ags in MS has been limited. More recently, other CNS Ags have been identified that are potential biomarkers in MS (19,20). The role of these Ags in MS pathogenesis is currently being further studied.…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…However, no additional bands (especially at 30 kDa) could be detected in the IP components resolved separately. Recently, another group has reported that CSF antibodies from some MS patients are reactive to triosephosphate isomerase (TPI), which is 27 kDa and glyceraldehyde-3-phosphate dehydrogenase (GAPDH), which is 37 kDa (Kolln et al, 2006). However, it is not possible that the identity of the ~30 kDa bands we observed in the immunoprecipitates could be TPI or GAPDH, because these proteins were not included in the IP components, and in the subsequent western blots, the primary antibody recognizes MBP specifically, and the secondary antibody recognizes antibody constant regions.…”
Section: The Mbp Reactive Fabs Precipitate Mbp In Solutionmentioning
confidence: 99%
“…Therefore, it is not surprising that any events that may impair the function of molecules involved in glucose metabolism could lead to significant damage in the integrity and function of neurons or their supporting cells. In this context, it is noteworthy that antibodies to AE, TPI, and GAPDH have been shown to be present in the CSF from MS patients (15,51,52). Besides their glycolytic roles, these enzymes also have other functions.…”
Section: Discussionmentioning
confidence: 99%